Barnard family papers - Barnard, Cyprion, 1753-; Barnard, Daniel D. (Daniel Dewey), 1797-1861.; Barnard, Ebenezer, 1727-1799.; Barnard, Ebenezer, 1748-1827.; Barnard, Harriet, 1787-1847.; Barnard, Timothy, 1756-1847.; Strong, Julia Barnard; Barnard, Ebenezer, 1748-1827.
Correspondence, bills, receipts, other business papers, memorandum books, account books, scrapbooks, genealogical notes, clippings, and photographs concerning business, social, and family life and including material on real estate, supply of the Continental Army, United States banking policies, tariff, the importation of textile and other machinery, and politics. Includes papers relating to frontier life and Eben Strong's ministry in Missouri, 1836-1839. Correspondents include Jonas Allen, Edward Gilbert, Chauncey Goodrich, John Mastic, and Gilbert Saltonstall.
Five generations of the Barnard (Bernard) family of Connecticut and western New York. Family members represented include Ebenezer Barnard, soldier, merchant, and shipowner; Ebenezer, Barnard, Jr., soldier, merchant, and land speculator; Cyprion Barnard, businessman; Timothy Barnard, Revolutionary commissary officer and judge; Harriet Barnard; Daniel D. Barnard, U.S. representative from New York and U.S. minister to Prussia (1850-1853); and Julia Barnard Strong, wife of clergyman Eben Strong.
Collection material in English.
Keywords: Allen, Jonas -- Correspondence; Gilbert, Edward, -- approximately 1819-1852 -- Correspondence; Goodrich, Chauncey, -- 1759-1815 -- Correspondence; Mastic, John -- Correspondence; Saltonstall, Gilbert -- Correspondence; Strong, Eben; Bernard family; United States. -- Continental Army -- Supplies and stores; Banks and banking -- United States; Clergy -- Missouri; Diplomatic and consular service, American -- Prussia (Germany); Frontier and pioneer life -- Missouri; Imports -- United States; Land speculation -- New York (State); Machinery; Merchants -- Connecticut; Merchants -- New York (State); Real estate investment -- Connecticut; Real estate investment -- New York (State); Shipowners -- Connecticut; Tariff -- United States; Textile machinery; Connecticut -- Politics and government; Connecticut -- Social life and customs; Missouri -- Church history; Missouri -- History; New York (State) -- Politics and government; New York (State) -- Social life and customs; United States -- History -- Revolution, 1775-1783 -- Equipment and supplies